Analisis Yuridis Tindak Pidana Pencucian Uang dari Hasil Kejahatan Penipuan Berdasarkan Hukum Positif di Indonesia (Nomor 395 K/Pid.Sus/2018) - Delia Permata Sari; Tantri Kartika; Papang Sapari (HUMANIORUM, 2023)
Money laundering crimes under the guise of investment occur a lot and it is very important to study and analyze them. Many losses arise due to money laundering practices, so efforts to prevent money laundering are needed. This study aims to analyze the Crime of Money Laundering in the Decision on Criminal Case No.395 K/Pid.Sus/2018. The type of research used is normative legal research. The charges handed down by the Public Prosecutor against the Defendant are Article 378 of the Criminal Code and Article 3 of Law No. 8 of 2010. With the decision Sentenced criminally to the Defendant therefore with imprisonment for 5 (five) years and a fine of Rp. 1,000,000,000, - (one billion rupiah) with the provision that if the fine is not paid it is replaced with imprisonment for 6 (six months).